Ethical Issues in Scientific Heritage M.M. Bakhtin. - Сломський, В. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The attention is focused on the direct analysis of the moral views of Bakhtin, which are closely linked with the peculiarities of his religiosity, which largely pomoget understand the specifics of his understanding of morality and innovative interpretation of the ethical sphere in its relationship with the culture of laughter. Thinker was inherent in a particular religion, which did not fit into the framework of even very broadly interpreted and revolutionary philosophers and cultural figures of "Silver Age" of orthodoxy. Bakhtin studied the idea that ethical values in the work of art must be subordinated to the aesthetic of objectivity. In order to create the aesthetic aspect of art was ultimately due to the height of value, it is necessary that the artistic interest of the author dominated by his cognitive and ethical interest.